IMIGRAÇÃO, RAÇA E CULTURA: o ensinamento de Franz Boas - Paltrinieri, Anna Casella (Outros Tempos: Pesquisa em Foco - História, 2009)
This article discusses the concepts of race and culture used today by the Italian authorities to justify the fight against foreign immigration. For both, the author uses some works of Franz Boas when analyzes the European immigration and especially Italian, in North America. This author, fighting the racist ideologies that were being formed at the beginning of the twentieth century in Europe, says that the crops should not be considered as variables of the same model, but as idiographic expressions of human creativity. Appears important the moral tension that trespass his scientific work, conceived as a way to get to the truth, a truth to be distributed "for not having lived in vain". These arguments are presents to read one of the most important authors of anthropological history.